2020
DOI: 10.1186/s12893-020-00747-2
|View full text |Cite
|
Sign up to set email alerts
|

Combining the use of Nuss procedure and rib fixation for severe flail chest: a case report

Abstract: Background: Severe flail chest is a life-threatening situation. The Nuss procedure is a new effective treatment for severe flail chest patients who cannot be weaned from prolonged mechanical ventilation in the last few years. However, the procedure is not suitable when there are multiple fractures in both the anterior and lateral chest walls. Here, we reported a rare case of severe flail chest in a patient who suffered multiple fractures in both the anterior and lateral chest walls in a traffic accident. Case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“… 7 Studies have also shown that surgical stabilization of fractured rib segments in the flail chest has statistically reduced the period of mechanical ventilation and its complications, pain, hospital stay, and thus being cost-effective along with improvement in long-term pulmonary function when compared to non-operative management. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Studies have also shown that surgical stabilization of fractured rib segments in the flail chest has statistically reduced the period of mechanical ventilation and its complications, pain, hospital stay, and thus being cost-effective along with improvement in long-term pulmonary function when compared to non-operative management. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“… 4 Associated injuries with flail chest may be pulmonary contusions, hemothorax, pneumothorax, head injury and occasional major vascular injury. 2 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the conventional procedure requires relatively long skin incisions and extensive tissue dissection. Several cases were reported previously in which the Nuss procedure was performed for surgical stabilization of flail chest with the same concerns ( Table 1 ) [ 8 - 16 ].…”
Section: Discussionmentioning
confidence: 99%